Juvenile hormone regulates the maturation of sexually dimorphic naive ethanol olfactory preference in Drosophila melanogaster - Antonio Marini-Davis; Ryan Oliver; Bailey Godwin; Sera Chase; Ziam Khan; Fernando J. Vonhoff (Royal Society Open Science)
The molecular mechanisms underlying the maturation of innate reward behaviours remain poorly understood. We have identified a sexually dimorphic innate reward behaviour in Drosophila melanogaster that varies depending on the age, sex and mating status in young adults. Our results suggest that the rewarding neuropeptide corazonin, the transcription factor apontic and juvenile hormone signalling regulate naive ethanol olfactory preference responses during early stages of adulthood. Pharmacological blockade of juvenile hormone via precocene increases naive ethanol olfactory preference in females and males, which is partially phenocopied by the knockdown of juvenile hormone receptors met and gce globally in the nervous system as well as specifically in the mushroom body. The observed changes in naive ethanol olfactory preference suggest a novel role of juvenile hormone in the maturation of dimorphic ethanol behaviours during the transition from increased naive ethanol olfactory preference observed in young flies to decreased naive ethanol olfactory preference responses in older flies. Mating decreases naive ethanol olfactory preference in males, likely acting through rewarding pathways such as neuropeptide F and corazonin. Our study suggests an early evolutionary emergence of hormonal mechanisms regulating ethanol-dependent behaviours, as corazonin and juvenile hormone functionally resemble the vertebrate gonadotropin-releasing hormone and thyroid hormones, respectively. The results described here pave the way for future studies to further investigate the molecular and cellular mechanisms by which a non-reproductive, yet sexually dimorphic behaviour matures using Drosophila as a model. The key molecular players identified to regulate this dimorphic behaviour are conserved among species, providing fundamental knowledge to advance our understanding of sexual dimorphism and brain maturation processes relevant in numerous species.